Математическое моделирование процессов структурообразования тонких пленок при низких температурах - Куценко, Александр Сергеевич; Марченко, Игорь Иванович (НТУ "ХПИ", 2013)
The mathematical model of the molecular dynamics method, which takes into account the effects of quantum statistics was formulated. Numerical scheme for the solution of the model was proposed. Test calculations and comparison with experimental data were obtained. The averaged is placements of copper surface atoms at different temperatures were computed.
Keywords: динамика молекулярная; статистика квантовая; модель математическая; расчеты тестовые